2015
DOI: 10.1002/pssb.201451507
|View full text |Cite
|
Sign up to set email alerts
|

GaInN‐based tunnel junctions with high InN mole fractions grown by MOVPE

Abstract: We demonstrated low‐resistive GaInN‐based tunnel junctions with high In mole fractions (over 0.35) grown by metalorganic vapor phase epitaxy (MOVPE). A 2 nm heavily Mg‐doped Ga0.6In0.4N/15 nm heavily Si‐doped GaN tunnel junction was grown on a standard‐sized (310 × 310 µm2) LED. The tunnel junction showed 0.06 V drop at 20 mA (26 A/cm2), corresponding to 4 × 10−3 Ωcm2 as the resistivity. This result indicates that MOVPE‐grown tunnel junctions showed an almost comparable resistivity as conventional p‐contact. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…One solution to this problem is forming a tunnel junction (TJ) for the anode contact of a deep-UV LED, because an n-type electrode with a low contact resistance is available. Table 1 lists previously reported LEDs having TJ-based anode contacts [20][21][22][23][24][25][26][27][28][29][30][31]. Some issues are faced in realizing a TJ-LED with a high-Al composition.…”
Section: Of 12mentioning
confidence: 99%
See 1 more Smart Citation
“…One solution to this problem is forming a tunnel junction (TJ) for the anode contact of a deep-UV LED, because an n-type electrode with a low contact resistance is available. Table 1 lists previously reported LEDs having TJ-based anode contacts [20][21][22][23][24][25][26][27][28][29][30][31]. Some issues are faced in realizing a TJ-LED with a high-Al composition.…”
Section: Of 12mentioning
confidence: 99%
“…Dehydrogenation from the p-type GaN layer buried under the n-type GaN has been reported to be difficult [35]. To avoid this problem, TJ layers were grown in the hydrogen-free ambient by methods such as plasma-enhanced molecular beam epitaxy (PAMBE) [20,22,[26][27][28][29][30] as it results in a lower differential specific resistivity (Rs) compared with that in the case of conventional MOVPE growth [21,[23][24][25]31]. Recently, Akasaka et al demonstrated the low resistivity of the n + -type GaN/p + -type GaN TJ using MOVPE growth by optimizing the doping profile and growth condition [25]; this should contribute toward the manufacture of GaN-based TJ contacts.…”
Section: Of 12mentioning
confidence: 99%
“…These cap layers are either p-type GaN layers [29] or n-type combined with tunnel junctions (TJs). [30][31][32][33][34][35] Thicker GaN cap layers are required for embedding an NW-MQS with a height of %1 μm. Therefore, p-GaN layers with high electrical resistance and high light absorption are not ideal cap layers.…”
mentioning
confidence: 99%
“…[21][22][23] Although a significant reduction in TJ voltage loss can be achieved in MOCVD grown TJs by taking advantage of high In mole fraction heterostructures, there is concern about optical absoprtion in the TJ layers when utilizing such TJ design in a cascaded LED structure. 24) It has been shown that some reduction in forward voltage can be achieved in MOCVD-grown TJs using growth interruptions that enable sharper doping profiles. 25,26) Through improvements in doping scheme and graded heterostructure design, visibletransparent MOCVD TJs with ultra-low voltage TJs (0.17 V at 100 A cm −2 ) were recently reported.…”
mentioning
confidence: 99%